KINETIKA ADSORPSI-REDUKSI ION Au(III) PADA ASAM HUMAT HASIL ISOLASI DARI TANAH GAMBUT RAWA PENING - Dian Prasasti; Sri Juari; Sri Sudiono (Pharmaciana, 2013)
Isolation of peat soil humic acid and its application for adsorption reduction of Au(III) have beenconducted. Humic acid was isolated from peat soil that was collected from Rawa Pening, Central Java. Isolation ofhumic acid from peat soil was based on conventional alkaline extraction method. Humic acid was extracted frompeat soil with NaOH 0.1 M, then precipitated with 0.1 M HCl, and purified with 0.1 M HCl/0.3 M HF 1/1. Theisolated humic acid was characterized by FTIR spectroscopy, then applied for adsorption and reduction process ofAu (III).Adsorption kinetics on adsorption reduction process of Au (III) also were studied. The gold metal formedwas confirmed by XRD diffractogram, and photo optical microscope. The adsorption rate constant (k) withSantosa kinetics model for humic acid is 0.0065 min-1.Peaks of gold particles in the difractogram are 2 = 38, 44,and 64.